Gender gap in voting: Evidence from actual ballots - Monika Köppl-Turyna (Agenda Austria, 2020)
This short article looks at the development of an electoral gender gap over time, using, for the first time, actual ballot data collected in the Austrian state of Vienna. Vienna recorded female and male ballots separately in the years from 1954 to 1991. Firstly, using this unique design, we conclude that the traditional gender gap (males more left-leaning) existed up to 1969 and then changed into the modern gender gap (females more left-leaning), from that date. These results confirm the considerable literature based on survey data. Secondly, we can confirm surveybased findings that male voters support more extreme positions than female voters. Thirdly, and contrary to expectations, we do not observe large systematic differences in turnout.
Keywords: D72; 330; electoral gender gap; ballots; Vienna; turnover